Perancangan Interior Lobby, Art & Craft CafÃ© di Hotel Allson City Makassar - Sriti Mayang Sari, Christina (Intra, 2014)
The expansion of tourism district, art and craft business and cafÃ© in Indonesia are moving vastly. This increase the demand of cafÃ©, retail and commercial hospitality. However, Makassar has not develop hotel, cafÃ©, and retail in a joined venture. Thus, it become the idea into design proposal of Art & Craft CafÃ© and Lobby of Allson City Hotel in Makassar. The aim of the design is to inform local and international visitors regarding the local culture by applying local content into the space. The proposal is themed âLive in Artâ, which translated literally as living into the art. The chosen concept is using post-modernism style which adopt the local art content into a contemporary design without leaving its character. The usage of local characteristics are including symbols and ornament of tongkonan, dominance of red, yellow, black and white which were adapted from Toraja culture. The application of local content into the proposal is including lobby area, which is the icon of the hotel, cafÃ©, as the lounge for visitors, and art and craft retail to support local arts. By applying local content that is modified with contemporary touch, designer aim to give its appeal for visitors whilst to prolong the local culture.